2015
DOI: 10.1158/1055-9965.epi-14-0804
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A and UGT2B Genetic Variation Alters Nicotine and Nitrosamine Glucuronidation in European and African American Smokers

Abstract: Background Identifying sources of variation in the nicotine and nitrosamine metabolic inactivation pathways is important to understanding the relationship between smoking and cancer risk. Numerous UGT1A and UGT2B enzymes are implicated in nicotine and nitrosamine metabolism in vitro; however, little is known about their roles in vivo. Methods Within UGT1A1, UGT1A4, UGT1A9, UGT2B7, UGT2B10, and UGT2B17, 47 variants were genotyped, including UGT2B10*2 and UGT2B17*2. The association between variation in these U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 57 publications
5
24
1
Order By: Relevance
“…A strong association was observed between the levels of urinary NNAL- N -Gluc and urinary nicotine-Gluc but not the O -glucuronidated metabolite of 3′-OH-cotinine in smokers in the present study, a pattern consistent with the N -glucuronidating capacity of UGT2B10 previously described in in vitro studies (20, 37, 39). …”
Section: Discussionsupporting
confidence: 91%
“…A strong association was observed between the levels of urinary NNAL- N -Gluc and urinary nicotine-Gluc but not the O -glucuronidated metabolite of 3′-OH-cotinine in smokers in the present study, a pattern consistent with the N -glucuronidating capacity of UGT2B10 previously described in in vitro studies (20, 37, 39). …”
Section: Discussionsupporting
confidence: 91%
“…19, 29 In addition, UGT2B17 glucuronidates 3HC, and racial differences in the activity of this enzyme have also been reported. 30 However, variation in 3HC glucuronidation was not found to be associated with NMR or nicotine intake 31 and we have no reason to believe that there is any association between genetically determined slow glucuronidation and low CYP2A6 activity. Thus, we believe it is valid to use [cotinine + 3HC] as a measure to examine the relationship between NMR and nicotine intake within race.…”
Section: Discussionmentioning
confidence: 80%
“…27, 38, 4244 Three enzymes, UGT1A9, 20, 45 UGT2B7 20, 45, 46 and UGT2B17, 40, 45, 47, 48 were previously found to mediate hepatic NNAL- O -Gluc formation in humans, with UGT2B17 exhibiting the lowest K M in vitro . While both UGTs 1A4 20, 27, 39, 45, 49 and 2B10 44, 45, 49 mediate NNAL- N -Gluc formation in humans, 27, 38, 39, 43, 50, 51 UGT2B10 was shown to account for ~95% of total hepatic NNAL- N -Gluc activity ex vivo. 49 …”
Section: Introductionmentioning
confidence: 99%
“…39, 40 This variation was suggested to be, in part, mediated by genetic polymorphisms in UGT2B17 and UGT2B10. Previous studies have shown that the prevalent UGT2B17 whole-gene deletion polymorphism [31-33% allelic prevalence in Caucasians] 48, 5254 and the UGT2B10 codon 67 Asp>Tyr SNP [9.1% allelic prevalence in Caucasians] 45, 55 are associated with large variability in hepatic NNAL- O -Gluc and NNAL- N -Gluc formation activities, respectively. 40, 44, 45, 48, 49 In addition, the UGT2B17 gene deletion polymorphism was significantly associated with lung cancer risk in women.…”
Section: Introductionmentioning
confidence: 99%